2012
DOI: 10.1186/1471-2393-12-70
|View full text |Cite
|
Sign up to set email alerts
|

The quality of antenatal care in rural Tanzania: what is behind the number of visits?

Abstract: BackgroundAntenatal care (ANC) provides an important opportunity for pregnant women with a wide range of interventions and is considered as an important basic component of reproductive health care.MethodsIn 2008, severe maternal morbidity audit was established at Saint Francis Designated District Hospital (SFDDH), in Kilombero district in Tanzania, to ascertain substandard care and implement interventions. In addition, a cross-sectional descriptive study was carried out in 11 health facilities within the distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
80
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 14 publications
15
80
2
Order By: Relevance
“…This study showed that 87.5% of respondents where not told about danger signs during pregnancy such as vaginal bleeding and 88% were not asked if she had headache. This is consistent with a study conducted in Tanzania in which in Fifty-two (20%) severe maternal morbidities were attributed to substandard ANC [12] 42% clients were not informed of any pregnancy danger signs. In this study permission was not taken before general and abdominal examination was done in 35% and 12% respectively.…”
Section: Discussionsupporting
confidence: 79%
“…This study showed that 87.5% of respondents where not told about danger signs during pregnancy such as vaginal bleeding and 88% were not asked if she had headache. This is consistent with a study conducted in Tanzania in which in Fifty-two (20%) severe maternal morbidities were attributed to substandard ANC [12] 42% clients were not informed of any pregnancy danger signs. In this study permission was not taken before general and abdominal examination was done in 35% and 12% respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Despite this change, as described in this study and in other African countries, women receive suboptimal services [2527]. This is of concern because it deprives women from receiving interventions that can improve their health, increase their awareness of potential complications and birth preparedness, and screen for conditions that could affect the newborn [6, 28].…”
Section: Discussionmentioning
confidence: 92%
“…To achieve maximum ANC services and practices among pregnancy women with high and low risk, there is a need to integrate public and private sector concerning ANC services planned and conducted in order to improve their maternal health and eventually improve the health status of newborn child. Empowered of women toward the primary level of education should be focused in order to have good maternal health outcome [36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%